Peristiwa 17 Oktober 1952: Tentara Pretorian Moderator dengan Gerakan Anti-Parlemen Pada Masa Kabinet Wilopo - Aldi Maulana; Ayi Budi Santosa (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2019)
This article aimed to analyze the relationship between civil government and military leader during the Wilopo Cabinet. The main issue was how did the soldiers’ attitude in the events of October 17, 1952, with the stance of the Anty-Parliament during the Wilopo Cabinet? The research method that used was the historical method which according to Helius Sjamsuddin, covering the collecting of the sources (heuristics), source criticism, and historiography. As for the results’ findings in this study is the intervention over the military internal’s matters and civil government which resulted in a worse relationship. Besides, the events of October 17, 1952, can be seen from different points of view, both the party pros and cons point of view by understanding the background of the occurrence of such events. Besides, reactions and responses after the events of October 17, caused friction in the internal military and civil government that could erode the country’sintegration. The soldiers’ attitude in the events put pressure on the civil government to give political policies that took a side but has no intention to take control of the civilian Government directly (The Pretorian of Moderators’ type).